The first case of rectal myxoid liposarcoma identified by FUS-DDIT3 fusion, presenting as a submucosal tumor with erosion - Hiroshi Kono; Yoshitane Tsukamoto; Shohei Matsuo; Hideki Hashidate; Hiroyuki Shibuya; Takashi Kobayashi; Yasumasa Takii; Seiichi Hirota (Elsevier, 2018)
We experienced a 58-year-old Japanese female complaining of bleedings at defecation for about one year. Endoscopy revealed an Ip submucosal tumor (SMT) at the rectum. Continuous bleedings at defecation and no evidence malignancy in a biopsy specimen led to a polypectomy. The specimen showed SMT with erosion, while the macroscopic cross-section implied a lipomatous mesenchymal tumor. Under the probable diagnosis of liposarcoma, especially myxoid liposarcoma, fusion-gene analyses were performed. The detection of type 1 FUS-DDIT3 fusion gene led to a definite diagnosis of rectal myxoid liposarcoma. For further treatment, a super low anterior resection was performed, revealing neither residual tumors nor lymph node metastases. The patient is now alive and free of disease for 5 years. To our knowledge of the literature, this is the first case of a rectal myxoid liposarcoma. Keywords: Rectum, Myxoid liposarcoma, Submucosal tumor